IMPLEMENTASI PENYELENGGARAAN ADMINISTRASI PENGUASAAN TANAH ATAS TANAH NEGARA DI KECAMATAN TENGGARONG KABUPATEN KUTAI KARTANEGARA - Aditiya Rakhman (Jurnal Paradigma (JP), 2021)
This study aims to determine and analyze the Administrative Policy of Land Tenure implementation over State Land in Tenggarong District, Kutai Kartanegara Regency. This research is qualitative research with informants selected by six people. We were collecting data using research, interviews, and library documentation. The results showed that the policy was running not optimal because there was no socialization of the stages of making SKPT to all residents, limited human resources, and no operational budget for land measurement.Keywords: policy, land administration, land tenure, state land